Analisis Peningkatan Upaya Pemungutan Pajak (Tax Effort) Kabupaten/Kota di Provinsi Jawa Tengah - Paramitha, Annisa Dwi; Rustam, Rinaldi (STIE Indonesia Banking School, 2024)
Regional Tax Collection Efforts in Indonesia are still low. There are only a few local governments in Indonesia with Tax Effort values ​​above the average. There is a unique fact that the 3 (three) regions that contribute the largest regional taxes in Indonesia (apart from DKI Jakarta), namely the regions in West Java, East Java and Central Java, actually have Tax Effort values ​​that are still below the average. flat. The aim of this research is to determine the influence of variables such as GRDP per capita, Development of the Manufacturing Industry Sector, Development of the Services Sector, Number of MSMEs, and Capital Expenditures on District/City Tax Effort in Central Java Province. The data used in this research is secondary and panel data. The research time span covers seven years, from 2017 to 2023, involving 35 districts/cities in Central Java Province. Data sources were obtained from the Ministry of Finance (Directorate General of Fiscal Balance) and the Central Statistics Agency. Data analysis in this research used multiple linear regression analysis. The results obtained showed that the development of the service sector and MSMEs had a positive impact on Regency/City Tax Effort in Central Java.